Diallel analysis of resistance in sorghum to greenbug biotype E: antibiosis and tolerance - Dixon, A.; Bramel-Cox, P.J.; Harvey, T. (Wiley, 1990)
The greenbug [Schizaphis graminum (Rondani)] has been recognized as a major insect pest of sorghum [Sorghum bicolor (L.) Moench] in the Great Plains of the USA since 1968. Biotype E has been prominent since 1980 and twelve sources of resistance within the Sorghum genus have been identified. The objective of this study was to investigate the inheritance of resistance in sorghum among seven sources of resistance and three susceptible lines for antibiosis and tolerance involving Biotype E. A complete diallel mating, including reciprocals, of the ten resistant and susceptible lines of sorghum was evaluated in the growth chamber to estimate heterosis, general combining ability (GCA), specific combining ability (SCA), maternal and specific reciprocal effects for seedling antibiosis, and tolerance to greenbug Biotype E. The majority of crosses between the resistant sources and susceptible lines showed intermediate reactions and various degrees of partial dominance for both antibiosis and tolerance, suggesting polygenic inheritance. Combining ability analyses revealed that GCA, SCA, maternal, and specific reciprocal effects were significant for both seedling antibiosis and tolerance, but GCA was clearly more important in determining tolerance. The most antibiotic parent, IS2388, had the largest GCA effect for antibiosis while the most tolerant parent PI 229828, had the largest GCA effect for tolerance. The significant maternal and specific reciprocal differences found among parents and crosses, respectively, suggested that the variation observed in this experiment was due not only to direct genetic effects, but also to maternal and/or cytoplasmic inheritance and specific interactions of cytoplasmic and genetic factors.